1990
DOI: 10.1136/thx.45.11.866
|View full text |Cite
|
Sign up to set email alerts
|

A general practice based survey of bronchial hyperresponsiveness and its relation to symptoms, sex, age, atopy, and smoking.

Abstract: The prevalence and associations of bronchial hyperresponsiveness were investigated in a general practice population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
2
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 28 publications
(8 reference statements)
6
53
2
1
Order By: Relevance
“…The sensitivity of mean slope to variation in baseline lung function and smoking between centres was investigated, as several authors have found that PD20 is dependent on baseline lung function [17][18][19][20][21] and related to smoking [21][22][23][24][25]. The average within-centre relationship of slope to baseline FEV1 and FEV1 % pred was used, and resulted in little change to the conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of mean slope to variation in baseline lung function and smoking between centres was investigated, as several authors have found that PD20 is dependent on baseline lung function [17][18][19][20][21] and related to smoking [21][22][23][24][25]. The average within-centre relationship of slope to baseline FEV1 and FEV1 % pred was used, and resulted in little change to the conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…TRIGG et al [36] investigated the role of age in airway responsiveness in a general practice population of 318 subjects (aged 18-75 yrs); again, airway hyperresponsiveness was not associated with increasing age, although it could be argued that the proportion of subjects showing airway hyperresponsiveness was higher in the oldest group (.30% in those aged 65-75 yrs versus f25% in the other study groups). The study also showed a strong negative association between airway hyperresponsiveness and baseline lung function.…”
Section: Airway Responsiveness and Age N Scichilone Et Almentioning
confidence: 99%
“…Measuring peak expiratory flow (PEF) variability has often been promoted as a good alternative for challenge testing [8]. Associations between PEF variability and bronchial responsiveness have been observed both in asthmatic and COPD patients [9][10][11][12], although the two phenomena are not interchangeable [9].…”
mentioning
confidence: 99%